The Role of Usul Al-Tafsir in Developing an Interdisciplinary Framework for Interpretation in the Modern Era - Yanti, Perdani; Azzizah, Nur; Hamidah, Nur; Habibah, Ummu; Sidik, Anwar (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This study aims to explore and analyze the role of ushul al-tafsir (the fundamental principles of Qur’anic exegesis) in shaping an interdisciplinary interpretative framework that is responsive to the challenges and needs of the modern era. Its main objective is to demonstrate how ushul al-tafsir can serve as a strong methodological foundation for integrating various disciplines in the interpretation of the Qur’an. This research employs a qualitative approach using library research methods. Data were obtained from classical and contemporary literature on ushul al-tafsir as well as modern interdisciplinary tafsir works. The analysis is conducted descriptively and analytically to identify the relevance and contribution of ushul al-tafsir to the development of crossdisciplinary interpretative methods, including social sciences, humanities, and natural sciences. The study finds that ushul al-tafsir provides a solid normative-methodological framework for addressing epistemological developments in tafsir. Ushul al-tafsir functions as a filter and guide in integrating contemporary sciences into the interpretative process without losing the authenticity of the Qur’anic message. By maintaining the classical fundamental principles of tafsir while remaining open to other scientific approaches, ushul al-tafsir can bridge the revealed text and the socio-modern context. This opens opportunities for the emergence of interpretations that are more contextual, solution-oriented, and adaptive to the developments of the times without deviating from the scientific integrity of Islamic knowledge.